2010
DOI: 10.1002/cbdv.200800320
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Adducts Formed in the Reactions of Malonaldehyde–glyoxal and Malonaldehyde–methylglyoxal with Adenosine and Calf Thymus DNA

Abstract: The reactions of adenosine with malonaldehyde and glyoxal, and with malonaldehyde and methylglyoxal resulted in the formation of one malonaldehyde-glyoxal and one malonaldehyde-methylglyoxal conjugate adduct, respectively. These adducts were isolated and purified by reversed-phase liquid chromatography, and structurally characterized by UV, (1)H- and (13)C-NMR spectroscopy, and mass spectrometry. The malonaldehyde-glyoxal adduct was identified as 8-(diformylmethyl)-3-(beta-D-ribofuranosyl)imidazo[2,1-i]purine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 36 publications
3
11
0
Order By: Relevance
“…M 1 Gx‐dA, M 1 MGx‐dA and M 1 Gx‐A were prepared according to previously described methods 14. Since the malonaldehyde‐glyoxal adduct of 2′‐deoxyadenosine, M 1 Gx‐dA, is formed in the relatively low yield, M 1 Gx‐A, the adenosine analogue of this compound was synthesised and used in the reaction with N α ‐acetyllysine carried out in preparative scale.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…M 1 Gx‐dA, M 1 MGx‐dA and M 1 Gx‐A were prepared according to previously described methods 14. Since the malonaldehyde‐glyoxal adduct of 2′‐deoxyadenosine, M 1 Gx‐dA, is formed in the relatively low yield, M 1 Gx‐A, the adenosine analogue of this compound was synthesised and used in the reaction with N α ‐acetyllysine carried out in preparative scale.…”
Section: Resultsmentioning
confidence: 99%
“…Such structures help to determine the mechanism responsible for the formation of these compounds. According to this mechanism, after Michael addition of the exocyclic amino group of the adenine nucleobase to the initially formed malonaldehyde‐glyoxal and malonaldehyde‐methylglyoxal conjugate respectively, the endocyclic N‐1 atom of the nucleobase attacks the carbonyl group of the conjugate that is derived from glyoxal and methylglyoxal, respectively 14. A similar situation likely takes place also in the case of formation of 3 ; the ϵ amino group of N α ‐acetyllysine attacks the carbonyl group of the opened form of hydrated M 1 Gx‐A that is derived from glyoxal but not from the α,β‐unsaturated aldehydic functionality derived from the malonaldehyde sodium salt.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we found that aldehydic adducts of adenine nucleosides 28,29 (Fig. 1) exhibit potent cross-linking activity.…”
mentioning
confidence: 97%